Alat Analisis Pemerintahan: Perspektif Kebijakan Ekonomi Lokal - Lesmana Rian Andhika (Jurnal Bina Praja, 2025)
Government analytical tools encompass various methodologies and strategies for evaluating, planning, and implementing public policies. This study investigates the various analytical tools local governments utilize and how these tools can be optimized to support local economic development. The literature review method was applied to identify related sources of information about the government’s analytical tools. The literature search was conducted across several indexed journal databases, including SCOPUS, WoS (Web of Science), EconPapers, and SINTA 2, to exclude journals with a negative reputation (predatory journals). This study identified 14 relevant articles using a predetermined method. The findings of this study indicate that there are obstacles, including limited human resources and bureaucratic pathology, which hinder the application of analysis tools by local governments. Comprehensive and diverse strategies are crucial for understanding the success of utilizing analytical tools in local economic development. This study is expected to attract the interest of government officials because the application of technological tools (such as applications) allows data to be extracted quickly and accurately, thereby expanding the scope of analysis. Additionally, utilizing government analytical tools can enhance transparency and accountability, providing deeper insight into the importance of high-quality data. Furthermore, future researchers can consider other analysis tools useful for local governments to visualize data as a guide for local economic development, such as the application of artificial intelligence (AI) and machine learning for predictive analytics development.